Rhynocoris persicus (Heteroptera, Reduviidae): Three Species or One? - Putshkov, P.V. (Вестник зоологии, 2002)
The study of type-specimens and other material demonstrates that Rhynocoris persicus (Jakovlev, 1877) = Rh. christophi (Jakovlev, 1877), syn. n. = Rh. analis (Jakovlev, 1889), syn. n. The two latter, as well as Rh. christophi f. pictipes (Horvath, 1911), are only melanistic forms of the former. The type of colour variability in Rh. persicus is similar to those in Rh. iracundus (Poda, 1761) and Rh. monticola (Oshanin, 1870). Key taxonomic characters and geographic range of Rhynocoris persicus (Jakovlev, 1877) as well as those of its infraspecific forms are reconsidered. The species inhabits not only the vast regions of the Fore Asia, but is present in Kazakhstan too. Besides other characters, its main differences from Rh. iracundus and other Rhynocoris species are the details of the aedeagal theca structure for male and the spindle-like incrassation of the hind tibia for female. The latter character as well as the wax-like substance covering this tibia may be associated with some unknown feature of the reproductive biology probably related to egg-deposition process. Изучение типов и других экземпляров показало, что Rhynocoris persicus (Jakovlev, 1877) = Rh. christophi (Jakovlev, 1877), syn. n. = Rh. analis (Jakovlev, 1889), syn. n. Два последних — лишь меланистические формы первого, как и Rh. christophi f. pictipes (Horvath, 1911). Вариабельность Rh. persicus по окраске подобна таковой Rh. iracundus (Poda, 1761) и Rh. monticola (Oshanin, 1870). Пересмотрены ключевые таксономические признаки Rhynocoris persicus (Jakovlev, 1877) в его новом пониманиии, равно как и данные о распространении вида и его форм. Вид не только населяет обширные регионы Передней Азии, но и присутствует в Казахстане. Помимо других признаков, его основные отличия от наиболее сходного Rh. iracundus и других видов Rhynocoris — детали строения теки пениса у самца и веретеновидное утолщение задних голеней у самки. Последний признак, как и воскоподобное покрытие этих голеней, вероятно, связаны с неизвестной особенностью репродуктивного поведения (при откладке яиц?).